suPAR: An Inflammatory Mediator for Kidneys - Yashwanth Reddy Sudhini; Changli Wei; Jochen Reiser (Karger Publishers, 2022)
Background: Inflammation is a common feature of many kidney diseases. The implicated inflammatory mediators and their underlying molecular mechanisms however are often not clear. Summary: suPAR is the soluble form of urokinase-type plasminogen activator receptor (uPAR), associated with inflammation and immune activation. It has evolved into a unique circulating kidney disease factor over the last 10 years. In particular, suPAR has multiple looks due to enzymatic cleavage and alternative transcriptional splicing of the uPAR gene. Most recently, suPAR has emerged as a systemic mediator for COVID-19 infection, associated with lung as well as kidney dysfunction. Like membrane-bound uPAR, suPAR could interact with integrins (e.g., αvβ3 integrin) on podocytes, providing the molecular basis for some glomerular kidney diseases. In addition, there have been numerous studies suggesting that suPAR connects acute kidney injury to chronic kidney disease as a special kidney risk factor. Moreover, the implication of circulating suPAR levels in kidney transplantation and plasmapheresis not only indicates its relevance in monitoring for recurrence but also implies suPAR as a possible therapeutic target. In fact, the therapeutic concept of manipulating suPAR function has been evidenced in several kidney disease experimental models. Key Messages: The last 10 years of research has established suPAR as a unique inflammatory mediator for kidneys. While open questions remain and deserve additional studies, modulating suPAR function may represent a promising novel therapeutic strategy for kidney disease.